2007
DOI: 10.1140/epjb/e2007-00135-2
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of canalizing Boolean networks

Abstract: Boolean networks with canalizing functions are used to model gene regulatory networks. In order to learn how such networks may behave under evolutionary forces, we simulate the evolution of a single Boolean network by means of an adaptive walk, which allows us to explore the fitness landscape. Mutations change the connections and the functions of the nodes. Our fitness criterion is the robustness of the dynamical attractors against small perturbations. We find that with this fitness criterion the global maximu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 19 publications
4
47
0
Order By: Relevance
“…[15]. More recently, works addressing the evolvability of robustness in BNs have been presented [1,5,27]. In the same direction is a recent paper, in which the global fitness function is defined as the sum of single functions, each related to a network parameter linked to network robustness [8].…”
Section: Design Methodologymentioning
confidence: 99%
“…[15]. More recently, works addressing the evolvability of robustness in BNs have been presented [1,5,27]. In the same direction is a recent paper, in which the global fitness function is defined as the sum of single functions, each related to a network parameter linked to network robustness [8].…”
Section: Design Methodologymentioning
confidence: 99%
“…In a multi-layer perceptron, for example, this might be done by scaling the output of a node's activation function. In a Boolean network, it would be similar to the use of canalising functions (such as AND) in which one or more inputs strongly determine a node's output [48], and which have been hypothesised to improve robustness by stabilising a network's attractors [99]. It also resembles multiplicative coupling in autocatalytic networks, a mechanism that allows nodes to exercise control over other nodes, and which is discussed in [27] in the context of connectionist architectures.…”
Section: Higher-order Functionsmentioning
confidence: 99%
“…The adaptive walk is a hill climbing process that leads to a local fitness maximum and thus can yield insights into the fitness landscape of a system. In [5], it was found that there is a huge plateau with the maximum fitness value that spans the network configuration space. Mutations change the connections and the update functions of the nodes.…”
Section: Network Evolved For Robustnessmentioning
confidence: 99%
“…In fact, it was found that networks that were generated by some evolutionary algorithm may have a very long but unique attractor that attracts all of state space [11], or that in such networks initially similar states may diverge at first exponentially fast but then converge to the same fixed point [5]. These are two examples where features of the 'frozen' and 'chaotic' phases are united within the same network.…”
Section: Introductionmentioning
confidence: 99%